Translational control by DHX36 binding to 5′UTR G-quadruplex is essential for muscle stem-cell regenerative functions - Xiaona Chen (Nature Portfolio, 2021)
Skeletal muscle stem cells (or satellite cells, SCs) are normally quiescent but activate and expand in response to injury. Here the authors show that induction of DHX36 helicase during SC activation promotes mRNA translation by binding to 5′UTR mRNA G-quadruplexes (rG4) in targets including Gnai2 and unwinding them.